ChemInform Abstract: Design, Synthesis, and in vitro hMAO‐B Inhibitory Evaluation of Some 1‐Methyl‐3, 5‐diphenyl‐4, 5‐dihydro‐1H‐pyrazoles. Issue 4 (28th January 2014) - Fioravanti, Rossella; Desideri, Nicoletta; Biava, Mariangela; Proietti Monaco, Luca; Grammatica, Laura; Yanez, Matilde
Abstract The synthesis of 30 title compounds of type (III) or (VI) is outlined and the compounds are screened for their inhibitory efficacy towards the two hMAO isoforms.